Barriers to care for children with orofacial clefts in North Carolina. Issue 11 (8th September 2014) - Cassell, Cynthia H.; Strassle, Paula; Mendez, Dara D.; Lee, Kyung A.; Krohmer, Anne; Meyer, Robert E.; Strauss, Ronald P.; Kirby, Russell; Browne, Marilyn
<x xml:space="preserve">Abstract</x> Background Little is known about the barriers faced by families of children with birth defects in obtaining healthcare. We examined reported perceived barriers to care and satisfaction with care among mothers of children with orofacial clefts. Methods In 2006, a validated barriers to care mail/phone survey was administered in North Carolina to all resident mothers of children with orofacial clefts born between 2001 and 2004. Potential participants were identified using the North Carolina Birth Defects Monitoring Program, an active, state‐wide, population‐based birth defects registry. Five barriers to care subscales were examined: pragmatics, skills, marginalization, expectations, and knowledge/beliefs. Descriptive and bivariate analyses were conducted using chi‐square and Fisher's exact tests. Results were stratified by cleft type and presence of other birth defects. Results Of 475 eligible participants, 51.6% (n = 245) responded. The six most commonly reported perceived barriers to care were all part of the pragmatics subscale: having to take time off work (45.3%); long waits in the waiting rooms (37.6%); taking care of household responsibilities (29.7%); meeting other family members' needs (29.5%); waiting too many days for appointments (27.0%); and cost (25.0%). Most respondents (72.3%, 175/242) felt "very satisfied" with their child's cleft care. Conclusion Although most participants reported being satisfied with their child's care, many perceived barriers to care were identified. Due to the limited understanding and paucity of research on barriers to care for children with birth defects, including orofacial clefts, additional research on barriers to care and factors associated with them are needed. Birth Defects Research (Part A) 100:837–847, 2014. © 2014 Wiley Periodicals, Inc.